2014
DOI: 10.1111/1346-8138.12693
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus pigmentosus‐inversus: Report of three Chinese cases and review of the published work

Abstract: Lichen planus pigmentosus-inversus is a rare variant of lichen planus. So far, only 24 cases from 12 reports have been documented in the published work. The prominent characteristics of the disease are dark-brown macules and patches confined to the non-sun exposed, flexural areas and skin folds with lichenoid pathological changes and prominent melanin incontinence. We report three female Chinese patients with typical clinical and pathological manifestations and a miniature review of the published work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 13 publications
4
37
1
Order By: Relevance
“…Histopathologically, the papule showed abundant lymphocytic infiltrates with the presence of histiocytes and melanophages beneath a flattened dermoepidermal junction and narrow epidermis. To date, case reports of LPPI have described macules, patches or plaques as being brown, dark‐brown, greyish‐brown or brownish in colour, and they have tended to describe pigmentary incontinence or melanophages in the upper dermis similar to the findings of Pock et al . We found that melanin granules were present not only in the dermis but throughout the epidermis in our patient, who had a similar clinical presentation.…”
supporting
confidence: 82%
“…Histopathologically, the papule showed abundant lymphocytic infiltrates with the presence of histiocytes and melanophages beneath a flattened dermoepidermal junction and narrow epidermis. To date, case reports of LPPI have described macules, patches or plaques as being brown, dark‐brown, greyish‐brown or brownish in colour, and they have tended to describe pigmentary incontinence or melanophages in the upper dermis similar to the findings of Pock et al . We found that melanin granules were present not only in the dermis but throughout the epidermis in our patient, who had a similar clinical presentation.…”
supporting
confidence: 82%
“…It predominantly affects women, mostly after 40 years, but has been described in individuals 15–82 years of age. LPP‐inversus affects fair and dark skin, with a worldwide distribution . Its pathogenesis is similar to LPP, but in LPP‐inversus a transition from papular LP to macular lesions of LPP has been observed.…”
Section: Lichen Planus Pigmentosus Inversus (Lpp‐inversus)mentioning
confidence: 99%
“…LPP‐inversus affects flexural areas, mainly the axillae, groin, submammary folds, and antecubital and popliteal fossae; however, the inner wrist, gluteal cleft, auricular sulci, abdominal folds, lumbar back, and neck can also be involved . It is characterized by dark brown to violaceous‐gray oval or linear macules with longitudinal axis along the lines of cleavage (Fig.…”
Section: Lichen Planus Pigmentosus Inversus (Lpp‐inversus)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lichen planus pigmentosus is difficult to treat given its resistant nature; however, it can improve spontaneously after several months [103,104]. Limited data exist on the successful treatment of LPP.…”
Section: Treatmentsmentioning
confidence: 99%